“Being Holistic Is a Lot to Ask”: A Qualitative, Cross-National Exploration of Occupational Therapists’ Perceptions and Experiences of Holistic Practice - Mona Asbjørnslett; Lisebet S. Skarpaas; Linda Stigen (Occupational Therapy International)
Being holistic is often used by occupational therapists to describe their practice and philosophy worldwide. This study explores the perspectives of 33 occupational therapists, working in 13 different countries, on their understanding of holistic epistemology and practice and how they seek to incorporate holism in their work. On the basis of a qualitative study design, individual interviews were conducted with the participants by 18 Norwegian undergraduate occupational therapy students, supported by their supervisors. The authors subsequently analyzed the transcribed data, using a thematic analysis approach. Three principal themes emerged: (1) holism as a broad and narrow concept, (2) being holistic spans from treating body parts to teaching marginalized children, and (3) being holistic is a lot to ask. When talking about holism and holistic practice, participants described their holistic practices in various ways, and their accounts reflected different understandings and cultural contexts. Participants characterized a holistic approach as one emphasizing the importance of occupations and activities and helping patients regain independence in their everyday lives. However, they also highlighted the specific challenges they faced, including cultural factors and inadequate resources. Significantly, participants from both Western and non-Western contexts emphasized the importance of holistic practice, suggesting that a dichotomous understanding of Eastern versus Western philosophical approaches does not necessarily make sense in occupational therapy interventions. Therapists’ degree of commitment to client-centered practice appears of greater relevance. With its international perspective, our study sheds light on important areas of contemporary occupational therapy practice, including the difficulties occupational therapists face when seeking to cover “everything” in an effort to be more holistic.